Supply Chain Driven Commercialisation of Bio Energy Carbon Capture and Storage - Klement, Jonathan; Rootzén, Johan; Normann, Fredrik; Johnsson, Filip (Frontiers in Climate, 2021)
Pulp mills, as large biogenic CO2 point sources, could adopt Bio Energy Carbon Capture and Storage (BECCS) through retrofitting carbon capture. These existing carbon sources constitute a great potential to roll out BECCS on commercial scale. Yet, despite political targets for negative emission production in Sweden, no incentive schemes were thus far enacted. While previous proposals focus on governmental compensation, the aim of this work is to set BECCS into the supply chain of a wide array of consumer products and thereby find alternative or complementary, business-driven, ways to incentivise BECCS when applied to the pulp and paper industry. In this work, we assess a ‘value proposition’ for low-carbon products in supply chains linked to the pulp and paper industry. By projecting the costs and negative emissions related to BECCS from the pulp mill to typical consumer products, as exemplified by three case study products, we show how BECCS can substantially reduce the carbon footprint of the consumer products, while only marginally increasing their cost. Additional price premiums could shorten the payback period of the initial investment in BECCS. The developed business case presents how actors along the supply chain for pulp and paper products can collectively contribute to securing financing and to mitigating investment risks. The results challenge the private sector, i.e. the companies along the pulp-and-paper supply chain to commit considerable investments also in the case without or with too weak direct political incentives. We conclude by discussing the governance implications on corporate and public level to enable the collaborative ‘bottom-up’ adoption of BECCS.